Libras e Língua Portuguesa: o bilinguismo em questão no curso de Letras-Libras da UFCG - Lima, Ritha Cordeiro de Sousa e (2024)
The initial training process of the deaf people has caused tensions, since the coexistence of different languages in this context requires, in addition to formal technical strategies that aim at the appropriation of linguistic codes, the reflection exercise about a curriculum culturally redefined. Based on that, I developed this study in a Brazilian sign language course focusing on deaf people. In order to better understand the Analytical Corpus, I used the epistemological view of cultural studies and studies of the deaf, because I consider they allow a better reading of the educational process that involves deaf people. I had as reference the following Investigative concerns: What are the implications that the course brings to people who are not fluent in the languages involved in the educational process (deaf and hearing people)? What theoretical and methodological requirements exist in the condition of Brazilian sign language of instruction? The data presented come from interviews in Brazilian sign languages with deaf participants and in Portuguese language with hearing participants. The results indicate that there are tensions strongly marked by subordinate bilingual context, especially concerning to the presence of the Portuguese language in the training processes regarding the exposure of deaf people.